2019
DOI: 10.1038/s41598-019-51777-7
|View full text |Cite
|
Sign up to set email alerts
|

Proteome and Secretome Dynamics of Human Retinal Pigment Epithelium in Response to Reactive Oxygen Species

Abstract: Age-related macular degeneration (AMD) is the leading cause of blindness in developed countries, and is characterized by slow retinal degeneration linked to chronic reactive oxygen species (ROS) in the retinal pigmented epithelium (RPE). The molecular mechanisms leading to RPE dysfunction in response to ROS are unclear. Here, human stem cell-derived RPE samples were stressed with ROS for 1 or 3 weeks, and both intracellular and secreted proteomes were quantified by mass spectrometry. ROS increased glycolytic p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 75 publications
(71 reference statements)
1
24
0
Order By: Relevance
“…Our above-mentioned results for metabolic function of stressed and crocetin-treated ARPE19 cells, are consistent with studies that showed RPE from AMD donors exhibit reduced mitochondrial and glycolytic function compared to healthy donors [81] and also confirm the suggestion of using therapeutic approaches to target RPE mitochondria as an effective strategy for AMD treatment [79][80][81][82][83]. However, our results for ATP production via glycolysis are in contrast to some studies that displayed an increase in glycolysis in RPE of AMD donors [78] and human stem cell-derived RPE cells stressed with Paraquat [84].…”
Section: Discussionsupporting
confidence: 92%
“…Our above-mentioned results for metabolic function of stressed and crocetin-treated ARPE19 cells, are consistent with studies that showed RPE from AMD donors exhibit reduced mitochondrial and glycolytic function compared to healthy donors [81] and also confirm the suggestion of using therapeutic approaches to target RPE mitochondria as an effective strategy for AMD treatment [79][80][81][82][83]. However, our results for ATP production via glycolysis are in contrast to some studies that displayed an increase in glycolysis in RPE of AMD donors [78] and human stem cell-derived RPE cells stressed with Paraquat [84].…”
Section: Discussionsupporting
confidence: 92%
“…Research has focused mostly on photoreceptor outer segment shedding, 74 as well as exosome 75 and glutamate uptake, 76 although C3 uptake by endocytosis 77 has been reported. Release of material includes the secretion of the RPE secretome, 78 and exocytosis contributes to the removal of phagocytic residual material at the basolateral plasma membrane if proper lysosomal degradation is inhibited. 79 Finally, uptake and release of C3H 2 O, which results from the slow spontaneous hydrolysis of the internal thioester bond of native C3, has been documented for ARPE-19 cells 64 as well as uptake of fH, 48 although polarity was not determined.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of POS phagocytosis, nicotinamide adenine dinucleotide phosphate oxidase or peroxidase in the phagocytic bodies will oxidize these fatty acids in POSs and generate large amounts of ROS [49]. Under stress conditions, photoreceptor cells have to metabolize constantly to renew their outer segments, which contribute to a unique source of ROS for RPE cells [50]. Moreover, RPE and photoreceptor cells contain higher levels of mitochondria, which are likely to produce more ROS than other cells [48].…”
Section: The Role Of Oxidative Stress In Amdmentioning
confidence: 99%